The LLLT Conundrum - Benjamin H. Barton (Washington University Journal of Law and Policy, 2025)
The United States faces a concerning lack of access to justice crisis. Most low and middle-income individuals are unable to afford adequate legal services. In response, several states have implemented Licensed Paralegal (LP) programs to allow non-lawyers to provide limited legal services. This article evaluates the viability and efficacy of LPs in addressing the justice gap by analyzing their regulatory frameworks, assessing the market viability, and reviewing practical limitations. LP programs face challenges such as restrictive practice limits, high licensing barriers, and competition from underemployed lawyers and unregulated paralegals. The analysis concludes that LP programs, as currently structured, are unlikely to significantly alleviate the crisis. Instead, this article advocates for alternative reforms that provide more promising solutions to the access to justice crisis. This may include integrating advanced technology, simplifying court processes, and adopting innovative business structures.
Keywords: AccessToJustice; LegalReform; LicensedParalegals